Design Optimization & Analysis of a Soft Crawling Robot - Md Ghazaly, Mariam; Mohd Basar, Siti Norazlin; Lagani, Muhammad Shadiq (International Journal of Integrated Engineering, 2021)
Robots are generally built by connecting rigid links and they have inadequate degree-of-freedom. The design of conventional rigid robots that are inadequate for the degree-of-freedom renders them unsafe for human dealings. Unlike the conventional robot, SCR (Soft Crawling Robots) having unique adaptive characteristics makes the robots fit in a confined space and make delicate movements. The design of such soft robots is usually inspired by living beings which results in the similarities of movements with the movements seen in living organisms. By focusing on the design as well as the actuation systems of such robots, they can be employed in real life purposes such as transportation and medical purposes. The robot’s primary structure is composed of material called the elastic elastomers. The SCR proposed design was created using the SolidWorks software. The SCR design has 2 variants which are Quadrupedal SCR and Inchworm SCR. The parameters of both kinds of robots are assessed by manipulating the base thickness, chamber gap distance, number of chamber and the air chamber width. Both designs are optimized using the FEM (finite element method). Assessment and optimization are carried out by using Abaqus to assess the robot’s performance with regards to the pressurized air.